2022
DOI: 10.3390/biomedicines10071644
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Is Associated with the Inhibition of Renal Artery AT1R/ET-1/iNOS Axis in a Rat Model of Diabetic Nephropathy with Suppression of Inflammation and Oxidative Stress and Kidney Injury

Abstract: Diabetes is the most common cause of end-stage renal disease, also called kidney failure. The link between the renal artery receptor angiotensin II type I (AT1R) and endothelin-1 (ET-1), involved in vasoconstriction, oxidative stress, inflammation and kidney fibrosis (collagen) in diabetes-induced nephropathy with and without metformin incorporation has not been previously studied. Diabetes (type 2) was induced in rats and another group started metformin (200 mg/kg) treatment 2 weeks prior to the induction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
0
12
0
2
Order By: Relevance
“…As regarding the inducible NO synthase, the drug has been reported to negatively regulate the iNOS expression in vascular smooth muscle cells treated with TNFα (28). In a very recent data, Dawood et al demonstrated the activation of renal artery angiotensin 1 receptor, upregulation of endothelin-1 and iNOS, as well as downregulation of eNOS in a rat model of diabetic nephropathy, effects that were reversed by Metf (29).…”
Section: Discussionmentioning
confidence: 99%
“…As regarding the inducible NO synthase, the drug has been reported to negatively regulate the iNOS expression in vascular smooth muscle cells treated with TNFα (28). In a very recent data, Dawood et al demonstrated the activation of renal artery angiotensin 1 receptor, upregulation of endothelin-1 and iNOS, as well as downregulation of eNOS in a rat model of diabetic nephropathy, effects that were reversed by Metf (29).…”
Section: Discussionmentioning
confidence: 99%
“…Препаратом першої лінії у лікуванні ЦД 2 типу з доведеними нефропротекторними властивості є цукрознижуючий засіб метформін. Показано, що захисна дія метформіну на нирки реалізується через різноманітні механізми, а саме зменшення глікозилування білків, посилення аутофагії, зниження активності запалення, оксидативного стресу, фіброгенезу та апоптозу [1,2,6,7]. У той же час практично відсутня інформація щодо ролі системи H 2 S у реалізації нефропротекторної дії метформіну.…”
Section: вступunclassified
“…За цих умов застосування метформіну виявляє нефропротекторну активність, яка характеризується зменшенням виразності нефросклерозу, гіпертрофії ниркових тілець, деструкції ендотелію, інтерстиційного запалення та пошкодження тубулярного апарату. Виявлені нами гістологічні зміни на тлі застосування метформіну не суперечать даним літератури при проведенні подібних досліджень [2,7].…”
Section: результати обговоренняunclassified
“…Metformin induced ovulation in nonobese women with PCOS better than the first-line drug for anovulatory infertility treatment, clomiphene [ 16 ]; (ii) metformin is widely used in clinical and research studies for cardiovascular and liver protection [ 17 , 18 ]. Metformin has been suggested to reduce body weight, inhibit the deposition of fats in blood vessels (atherosclerosis), improve hemostatic function and immune cell performance, and protect against nonalcoholic steatohepatitis-induced hepatocellular carcinoma [ 17 , 18 ]; (iii) metformin also prevents apoptosis and cellular deterioration with age (senescence) in intervertebral disc degeneration via autophagy stimulation through the activation of AMPK, which ameliorate the degeneration of discs in vivo [ 19 ]; and (iv) metformin ameliorates several types of kidney diseases such as autosomal dominant polycystic kidney disease and acute kidney injury; reduces mortality in patients with CKD, diabetic nephropathy [ 20 , 21 ], and gentamicin-induced nephrotoxicity via reducing mitochondrial ROS and hence improves mitochondrial homeostasis [ 22 ] in patients with stable chronic renal impairment [ 23 ]; and, finally, metformin was reported to decrease the risk of death in patients with kidney cancers and localized and metastatic renal cell carcinoma [ 24 ]. Therefore, this study examined if metformin can protect against TAA-induced kidney injury and fibrosis in rats using physiological and biochemical methods, basic and special histology staining, immunoblotting, and real-time PCR (to assess the relative gene expression) to test the proposed working hypothesis.…”
Section: Introductionmentioning
confidence: 99%